Influence of match quality on men`s volleyball performance at different competition levels - Garcia-de-Alcaraz, A.; Marcelino, R. (International Journal of Performance Analysis in Sport, 2017)
Performance in team sports is the result of a dynamic and interactive process between two opposing teams. The aim of this study was to examine the performance of volleyball players executing terminal actions (i.e. serve, attack, block and counter-attack) in terms of match quality. Three hundred and seven sets were selected randomly from U14s up to Olympic level and analysed according to type of match: balanced (strong vs. strong, and weak vs. weak teams) and unbalanced matches (strong vs. weak). The variables analysed were: competition category, frequency of use and coefficient of efficacy for each technical-tactical action, and way of execution in terms of match quality. A K-means cluster analysis was performed to divide teams into two groups according to quality (stronger or weaker teams). The change between the types of match was estimated by means of effect size at 90% confidence intervals. Few and small differences between balanced and unbalanced matches were found. Most changes were related to play style, and happened in balanced matches and in initial age categories. The findings may be useful for coaches, physical trainers and match analysts when evaluating team performance and designing plans according to competition demands and players` stages of development.